Reliability and validity of the Persian version of Work-Family Conflict Scale - Gholamreza Rajabi; Enayat Makki; Khald Aslani (Payesh, 2020)
Objective (s): The work-family conflict is a form of conflict that a person feels inconsistency between the demands of his or her role and the demands of the family role. The aim of the current research was to translate and assess reliability and validity of the Persian version of Work-Family Conflict Scale. Methods: Forward-backward procedure was applied to translate the Carlsonchr('39')s Work-Family Conflict Scale from eglish into Persian. 146 participants from Shahid Chamran University and 132 participants from Jondi Shapour Medical Sciences University of Ahvaz (278 in total) were selected and completed the questionnaire. The data were analyzed using the exploratory factor analysis. Results: The results obtained from exploratory factor analysis using principal components (varimax rotation) identified three factors: work-family and family-work conflict based on time, work-family and family-work conflict based on strain, and work-family and family-work conflict based on behavior. The Cronbachchr('39')s α coefficients for the entire scale and the factors obtained 0.86, 0.85, 0.84, and 0.88, respectively. The correlation coefficients between each item and the entire scale ranged from 0.40 to 0.65 (p < 0.001) and the divergent validity coefficients of the scale with the Multidimensional Perceived Social Support and the Marital Satisfaction Scales were negatively significant - 0.72 and - 0.62, respectively. Conclusion: The findings suggest that the Persian Work-Family Conflict Scale is valid and can be used in future studies.